VACCINATION OF PREMATURE/LOW-BIRTH-WEIGHT CHILDREN - V. K. Tatochenko (Union of pediatricians of Russia, 2013)
The article is dedicated to vaccination of premature/low-birth-weight children. This is an extremely topical issue as these children are the most susceptible to infectious diseases, including controlled diseases; however, specialists are reluctant to vaccinate them due to possible unfavorable responses of premature bodies to the introduction of an immunotropic agent. The authors present peculiarities of immune response of premature infants, of the T-cell level in particular, which are to be taken into account during vaccination. Special attention is given to the safety of vaccines - risk of development of apneic episodes with/without bradycardia, their influence on the frequency of obstructive episodes and effect of simultaneous introduction of several vaccines on body. Moreover, the article sets forward issues of immunogenicity and reactogenicity of various vaccines when administered to low-birth-weight children.